Life cycle assessment of power generation alternatives for a stand-alone mobile house - ÇİFTÇİOĞLU, GÖKÇEN ALEV (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
This paper presents comparative life cycle assessment of nine different hybrid power generation solutions that meet the energy demand of a prototypical mobile home. In these nine solutions, photovoltaic panels and a wind turbine are used as the main energy source. Fuel cell and diesel generator are utilized as backup systems. Batteries, compressed H-2, and H-2 in metal hydrides are employed as backup energy storage. The findings of the study shows that renewable energy sources, although they are carbon-free, are not as environmentally friendly as may generally be thought. The comparative findings of this study indicate that a hybrid system with a wind turbine as a main power source and a diesel engine as backup power system is the most environmentally sound solution among the alternatives. Copyright (C) 2013, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Wind; Solar; Fuel cell; Life cycle assessment; Stand-alone; Hybrid power; INTERNAL-COMBUSTION ENGINE; ASSESSING FUTURE ENERGY; FUEL-CELL; ENVIRONMENTAL IMPACTS; TRANSPORT-SYSTEMS; PV SYSTEMS; COST; PERFORMANCE; MANAGEMENT; VEHICLES